Pengaruh Pelatihan Kerja, Insentif dan Disiplin Kerja Terhadap Kinerja Karyawan - febri amalia zen; M. Mansur; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe aim of this study was to know the influence on training of work, incentive and discipline of work toward the emp loyee performance of PT FIFGROUP Batu. The subject of the study was from the employee of PT FIFGROUP Batu that consists of 47 respondents. The method of collecting data in this study used census method, also statistical analysis and multiple linear regression analysis are used in this study.            Based on the result of multiple linear regression analysis can be known that training of work was significant effect on the employee performance of PT FIFGROUP Batu, incentive insignificant effect on the employee performance of PT FIFGROUP Batu. Discipline of work was significant effect on the employee performance of PT FIFGROUP Batu. Keywords : Training of work, incentive, disclipline of work and the employee performance.